2019
DOI: 10.1186/s12887-019-1874-z
|View full text |Cite
|
Sign up to set email alerts
|

Communication between mothers and health workers is important for quality of newborn care: a qualitative study in neonatal units in district hospitals in South Africa

Abstract: BackgroundThere is a high global burden of neonatal mortality, with many newborn babies dying of preventable and treatable conditions, particularly in low and middle-income countries. Improving quality of newborn care could save the lives of many thousands of babies. Quality of care (QoC) is a complex and multifaceted construct that is difficult to measure, but patients’ experiences of care are an important component in any measurement of QoC. We report the findings of a qualitative study exploring observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 33 publications
1
35
0
3
Order By: Relevance
“…One study showed parents perceived providers as being rude or withholding information or not listening to mothers; non-consented care; speaking loudly about baby’s condition without consideration for privacy and confidentiality. On the other hand providers’ described mothers not following instructions (not washing hands prior to entering neonatal unit); giving incorrect or misleading information "lying about the condition" to have their baby discharged sooner [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed parents perceived providers as being rude or withholding information or not listening to mothers; non-consented care; speaking loudly about baby’s condition without consideration for privacy and confidentiality. On the other hand providers’ described mothers not following instructions (not washing hands prior to entering neonatal unit); giving incorrect or misleading information "lying about the condition" to have their baby discharged sooner [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Processes that support mothers and fathers to learn how to care for their premature babies while still in hospital in readiness for caring for their babies at home was described as a positive experience of care. This helped parents overcome their fears and insecurities, strengthen mother-infant bonds, and made them feel empowered to participate actively, in the care of their babies and increased confidence of caregiving at discharge [ 32 , 34 ]. Positive experiences of parents, including providers responding to their needs and rights, was also instrumental in improving a child’s ability to thrive.…”
Section: Resultsmentioning
confidence: 99%
“…A garantia deste processo efetivo de interlocução também permite investigar a qualidade do acompanhamento implementado por ambos os serviços de saúde (atenção primária e ambulatório de alto risco). Porém, nem todos os trabalhadores dos serviços de saúde têm consciência acerca da sua importância no cumprimento desse papel, tornando essencial o treinamento dos profissionais de saúde para uma boa comunicação, aumentando, assim, as possibilidades de um cuidado integrado entre os serviços da rede de atenção (18) .…”
Section: Discussionunclassified
“…A sample size of 20 participants was estimated as enough to reach data saturation, based on our previous experience conducting qualitative research [ 32 , 33 ]. Twenty-four informal working women were enrolled in the cohort to allow for loss to follow-up over the extended period of follow up.…”
Section: Methodsmentioning
confidence: 99%